What issues bring primary school children to counselling? A service evaluation of presenting issues across 291 schools working with Place2Be. Issue 4 (5th July 2020) - Toth, Katalin; Samad, Lamiya; Golden, Sarah; Johnston, Patrick; Hayes, Rachel; Ford, Tamsin
Abstract: Background: Poor mental health reduces children's ability to function at school, which in turn may undermine their mental health. The provision of school‐based counselling aims to help schools to support their pupil's mental health. Most work on the types of difficulties brought to school counsellors has focused on secondary school pupils (aged 11 years or over), and to our knowledge, this is the first study of presenting issues in younger children. Method: Data were systematically collected using a list of 21 potential presenting issues during assessment and formulation of 8, 893 children referred for counselling in 291 UK primary schools over 3 years. We explored the number, severity and types of presenting issues recorded by counsellors in the whole sample by gender. Results: The children assessed by counsellors had higher levels of known correlates for poor mental health than their peers in the same schools. Most children had multiple presenting issues, while 55% of children had at least one severe presenting issue. The commonest presenting issues were generalised anxiety, low self‐esteem, family tensions and mood swings. Girls were more likely to present with all types of anxiety and family tensions, while attentional problems and mood swings were commoner among boys. Conclusions: Children referred for counselling in primary schools often present with multiple difficulties, which are often severe. This indicates the need for systematic and detailed assessment, adequate training and supervision and good links with external agencies.